Analisis Carbon Footprint Gedung Perpustakaan Pusat, Rektorat, dan Lab. Mipa Uii Berbasis Vegetasi Eksisting Sebagai Pereduksi Emisi Gas Rumah Kaca - Yulianto Purwono Prihatmaji; Akhmad Fauzy; Syaiful Rais; Feris Firdaus (Asian Journal of Innovation and Entrepreneurship, 2016)
Global warming is the increase in the average temperature of the atmosphere, ocean and land earth. Global warming can occur due to the greenhouse effect. Problems arise when the concentration of greenhouse gases in the atmosphere increases. With increasing concentrations of greenhouse gases, the more heat retained surface of the earth and will cause the earth's surface temperature to rise. Increased temperatures also happened in Yogyakarta. The air is cool before now turned into more heat. One cause of greenhouse gas emissions is carbon dioxide which is currently the biggest contributor came from the center of fossil-fueled power plants. In particular the research conducted is to calculate the carbon dioxide emissions (carbon footprint) resulting from a building to measure the adequacy of existing vegetation as reducing greenhouse gas emissions. The carbon footprint is calculated that the energy consumption of the electricity sector in the Central Library building, solids, and Lab. MIPA UII Yogyakarta. The method used in the calculation of the carbon footprint of electricity consumption of data collection, electronic instruments, and absorption of existing vegetation which then calculated the carbon footprint dioxide emissions generated by absorption of existing vegetation. The results of both calculations are then compared to determine the adequacy of the existing vegetation to absorb carbon dioxide emissions. From the results of the calculation are compared, it is known that the absorption of vegetation existing in the building of the central library is able to absorb emissions by 80% of the total carbon dioxide emissions generated at 4548 kg / year, the absorption of vegetation in rectorate building for 50% of carbon dioxide emissions by 1980 kg / year, and the absorption of vegetation in mathematics and natural sciences laboratory building at 3120 kg/year. The comparison showed that the existing vegetation in the objects of research proficiency level sufficient to absorb the carbon dioxide emissions resulting from the energy sector of the electricity consumed.